Effect of silvicultural management on the Nothofagus dombeyi, N. alpina and N. obliqua forest regeneration within the Lanín Natural Reserve (Argentina) - Sola, Georgina; Attis Beltrán, Hernán; Chauchard, Luis; Gallo, Leonardo (Bosque (Valdivia), 2017)
Management practices are important disturbance agents at local level and their incorrect implementation may affect the sustainability of natural forests. Usually, silviculture based on the shelterwood system was carried out in the mixed stands composed of Nothofagus dombeyi, N. alpina and N. obliqua, located at Lanín Natural Reserve (Neuquén Province, Argentina). However, the effect of this scheme on the composition and structure of natural regeneration is still rather unknown. In this study, composition, age, abundance and spatial pattern of adults and saplings of Nothofagus species were evaluated in a 3-ha plot logged in 1993. At pre-harvest period, adult density was 26 % for N. dombeyi, 38 % for N. alpina and 35 % for N. obliqua. Regeneration consisted mainly of N. nervosa. After logging, composition of adult trees was 20 %, 43 % and 37 % for N. dombeyi, N. alpina, N. obliqua, respectively; whereas regeneration was 45 % for N. obliqua and 42 % for N. dombeyi. Within species, no relationship was found between basal area of adult trees and density of saplings. For all tree species, age regeneration was larger in areas where tree canopy cover exhibited higher values. N. alpina was the last installed species. Preservation of the relative species composition after logging did not maintain the original abundance within regeneration. Consequently, it is necessary to adjust silvicultural practices, and particularly the level of canopy openings, in order to maintain species composition unaffected as a key indicator of sustainability at management unit scale.